Analisis Pemilihan Guru Konseling dengan Metode VIKOR pada SMK TPI Alhasanah Pematang Bandar - Delima Syah Putri Sinaga; Sundari Retno Andani; Dedi Suhendro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study aims to determine the right counseling teacher at SMK TPI Al-Hasanah to be able to help, direct and change the deviant behavior of students that occur in the school environment. The decision support system applied in this study is by using the VIKOR method. The data obtained in this study by direct observation to the field and also requesting accurate data from the leadership. The selection of counseling teachers is done with several criteria. The criteria are: (K1) last graduation, (K2) Length of Work, (K3), Discipline, (K4) Supporting certificates. It is expected that the results of this research using the VIKOR method can determine appropriate counseling teachers and be able to direct students at SMK TPI Al-Hasanah to become more virtuous individuals both in the school environment and also in the community